Electrochemical Behavior of Malachite Green in Aqueous Solutions of Ionic Surfactants. (30th September 2013) - Rahman, Mohammad Mijanur; Mollah, M. Yousuf A.; Rahman, M. Muhibur; Susan, Md. Abu Bin Hasan
Abstract : Electrochemical behavior of malachite green (MG) oxalate in aqueous solution was studied in the presence of a cationic surfactant, cetyltrimethylammonium bromide (CTAB), and an anionic surfactant, sodium dodecyl sulfate (SDS) at a glassy carbon electrode using cyclic voltammetry. The electrochemical oxidation of MG has been characterized as an electrochemically irreversible diffusion-controlled process. Oxidative peak current sharply decreased with increasing SDS concentration, while a slight increase with increasing [CTAB] was apparent. The apparent diffusion coefficient, the surface reaction rate constant, and the electron transfer coefficient of MG clearly show correlation of the electrochemical behavior with the dissolved states of the surfactants. Electrochemical observations together with spectrophotometric results at varying surfactant concentrations provide evidence of interaction of MG with the surfactants to varying extent depending on the type of the surfactant and the concentration.